2022
DOI: 10.3390/ijms23137408
|View full text |Cite
|
Sign up to set email alerts
|

Do Extracellular Vesicles Derived from Mesenchymal Stem Cells Contain Functional Mitochondria?

Abstract: Extracellular vesicles (EV) derived from stem cells have become an effective complement to the use in cell therapy of stem cells themselves, which has led to an explosion of research into the mechanisms of vesicle formation and their action. There is evidence demonstrating the presence of mitochondrial components in EV, but a definitive conclusion about whether EV contains fully functional mitochondria has not yet been made. In this study, two EV fractions derived from mesenchymal stromal stem cells (MSC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…In addition, it has been recently shown that EVs contain biologically active cytokines that could be released from these vesicles to their targeted cells by a yet uncharacterized mechanism [ 45 ]. Recent reports also showed that EVs generated ex vivo contain functional mitochondria [ 46 , 47 , 48 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…In addition, it has been recently shown that EVs contain biologically active cytokines that could be released from these vesicles to their targeted cells by a yet uncharacterized mechanism [ 45 ]. Recent reports also showed that EVs generated ex vivo contain functional mitochondria [ 46 , 47 , 48 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Emerging evidence indicates the presence of mitochondrial components in EVs [ 40 ]. As known, Glo2 is also located in the mitochondrion [ 7 ], which might suggest a mitochondrial origin for EV-embedded Glo2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hsp27 have been found to be exported by exosomes, playing a key role in cell-to-cell communication, signaling, immunity, and inflammation. Interestingly, Hsp27 also plays a pivotal role in the biogenesis of exosomes [ 40 ]. We speculate that MG-modified Hsp27 may be endowed with a major functionality in performing the above-mentioned biological roles, which remain to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of EVs is further increased when we consider other structures, such as apoptotic bodies released from cells undergoing apoptosis, which can span over a large size range (from 100 nm to 5 µm in diameter) [ 25 ], or the recently identified mitovesicles from mitochondrial origin [ 26 ]. Interestingly, recent studies revealed that EVs could even transport whole organelles inside them, such as mitochondria, thus enabling their functional trafficking between cells [ 27 , 28 ]. Both the trafficking of mitovesicles, or whole mitochondria shuttled inside EVs, seem to be associated with the processes of mitochondrial regulation and dysfunction, namely in neurodegenerative disorders.…”
Section: Ev Biologymentioning
confidence: 99%